William Lashly: An Appreciation - Cherry-Garrard, Apsley (Polar Record, 1940)
Lashly is dead. He was a Chief Stoker in the Navy, and he was one of the last survivors who served on both of Scott's Antarctic expeditions. Scott, Wilson, Bowers, Titus Oates, Atkinson and Wild—all are gone; and Crean who died about a year ago, and Pennell as good as any of them.